Analysis of 7,13-Bis((8-hydroxy-2-quinolinyl)methyl)-1,4-dimethyl-1,4,7,13-tetraaza-10-thiacyclopentadecane by XPS - Hoggard, Jamin (2004)
Highly toxic metals abound in the environment as a result of pollution. Macrocyclic ligands have been designed that are selective in binding certain toxic metals. This allows for a sensitive means of detecting these poisonous metals. Here we report the XPS analysis of 7,13-bis((8-hydroxy-2-quinolinyl)methyl)-1,4-dimethyl-1,4,7,13-tetraaza-10-thiacyclopentadecane.